Analisis terhadap FaktorâFaktor Penentu Perilaku Kepatuhan Pajak dalam Konsep Islam - Bulutoding, Lince (Patria Artha University, 2017)
The concept of obedience in Islam always calls for obedience to God and His apostles and to ulil amri or leader (Quran 4:59). Obedience to the leader is one form of obedience to God as long as it is not immoral (Sadi, 2015b: 103; and Shihab, 2012b: 584). Obedience to leaders can also mean compliance in the fulfillment of obligations to the state in terms of taxes. The behavior of tax compliance is a form of obedience to Allah and His Messenger. The purpose of this study is to examine the determinants of compliance behavior of taxpayers, adjusted to the values believed in Islam. Research method in this research is exploratory research by using factor analysis to 285 taxpayers in Malaysia, with the number of variables analyzed by 29 variables. Based on the result of factor analysis, this research shows that there are 19 variables that have loading factor above 0.40 by forming 6 (six) factors formed.